Model for Alliance Partners Selection Based on the Grey Model and DEA Application-Case by Vietnamese Bank Industry - Thanh Van Phan; Nan Chia Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Facing the operational inefficiency situation during a long time, the sharply blooming of small domestically banks and the banking bad debt situation increase year by year, all elements have reduced their competiveness. Therefore, how enhancing their competitiveness? This study based on the Grey forecasting modeling (GM) and Data Envelopment Analysis (DEA) as foundation proposes an effective approach for helping manager find out the best partner when formed alliance. Realistic data of 21 banks were collected from the Vietnam stock exchange, the state bank of Vietnam and their official website, the empirical study indicates that there are 6 the best combinations in the total of 210 virtual alliances. These results are good sound for helping organization to select the best candidates when implementing alliance. This issue can be extended and applied in many fields by considering lots of different factors in the future.